2023
DOI: 10.1002/advs.202301697
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR Assays for Disease Diagnosis: Progress to and Barriers Remaining for Clinical Applications

Abstract: Numerous groups have employed the special properties of CRISPR/Cas systems to develop platforms that have broad potential applications for sensitive and specific detection of nucleic acid (NA) targets. However, few of these approaches have progressed to commercial or clinical applications. This review summarizes the properties of known CRISPR/Cas systems and their applications, challenges associated with the development of such assays, and opportunities to improve their performance or address unmet assay needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 201 publications
(197 reference statements)
0
3
0
Order By: Relevance
“…This sensitivity is insufficient for the direct detection of uveal melanoma mutations from either tumor tissue or liquid biopsy. Cas12a sensing must then be coupled to prior nucleic acid amplification . Among the different amplification techniques available, we chose PCR because it is a cost-effective, specific, and semiquantitative method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This sensitivity is insufficient for the direct detection of uveal melanoma mutations from either tumor tissue or liquid biopsy. Cas12a sensing must then be coupled to prior nucleic acid amplification . Among the different amplification techniques available, we chose PCR because it is a cost-effective, specific, and semiquantitative method.…”
Section: Resultsmentioning
confidence: 99%
“…Cas12a sensing must then be coupled to prior nucleic acid amplification. 22 Among the different amplification techniques available, we chose PCR because it is a costeffective, specific, and semiquantitative method. To assess the potential suitability of our strategy for detecting GNAQ Q209P from physiological samples, we isolated genomic DNA (gDNA) from two cell lines: OMM 1.3, a uveal melanoma cell line containing the GNAQ Q209P mutation; and HEK293, a cell line with wild-type GNAQ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…CRISPR-Cas systems are extensively employed in nucleic acid testing (NAT), leveraging the trans-cleavage activity of Cas proteins activated by CRISPR RNA (crRNA) targeting. 1 Previous studies have primarily focused on harnessing Cas13's trans -cleavage activity towards ssRNA, and relatively complex strategies are required to ultimately achieve essential sensitivity for target amplification-free detection (Table S1, ESI†). 2–4 We previously uncovered that Cas12a can trans -cleave DNA G-quadruplex (G4) and G-triplex (G3) structures, and demonstrated that the high-order DNA structure-based reporter improved the detection sensitivity by up to 20 fold for NAT (albeit without a fully disclosed mechanism).…”
mentioning
confidence: 99%